M-Learning: Using Telegram To Engage And Gamify Esp Learning - Ramamurthy, Lena; Shafien, Syakirah; Mohd Nawi, Noor Syamimie; Omar, Suhaida (2019)
The advent of smartphone is surging through all spheres of life, especially among the young adults. The use of smartphone is no doubt revolutionizingthe field of education as well. Knowing the fact that social media has become part and parcel of the young adults' life, integrating Telegram into ESP learning is of great importance. Incorporate the use of Telegram in ESP learning is said to be a valuable extension of traditional ESP learning methods and also to leverage the advantages in ESP learning.